2012
DOI: 10.22358/jafs/66137/2012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diets enriched in omega-3 fatty acids on carcass characteristics and the fatty acid profile of intramuscular and subcutaneous fat in pigs

Abstract: The objective of this study was to determine the effect of the concentration of C18:3 n-3 and the total concentration of polyunsaturated fatty acids (PUFA) and n-3 PUFA in the diet on the performance of pigs, carcass characteristics, and fatty acid profile of intramuscular fat of Musculus longissimus dorsi (MLD) and subcutaneous tissue (ST) fat. Twenty-four crossbred pigs ♂Duroc x ♀(Polish Large White x Danish Landrace) were divided into 3 groups (A, B, and C) and from 60 to 105 kg body weight (BW) were fed is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 20 publications
6
8
1
Order By: Relevance
“…Regarding PUFA deposition, it is interesting that Wojtasik et al (2012), when fattening pigs with a diet containing 2.5% of linseed oil + 1% of fish oil, reported higher PUFA/SFA ratio in a subcutaneous fat than in a muscle tissue (m. longissimus dorsi), which is contrary to our finding: the PUFA/SFA ratio was 0.58 in the VAT and 0.70 in the muscle tissue (m. quadriceps femoris) in the present experiment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding PUFA deposition, it is interesting that Wojtasik et al (2012), when fattening pigs with a diet containing 2.5% of linseed oil + 1% of fish oil, reported higher PUFA/SFA ratio in a subcutaneous fat than in a muscle tissue (m. longissimus dorsi), which is contrary to our finding: the PUFA/SFA ratio was 0.58 in the VAT and 0.70 in the muscle tissue (m. quadriceps femoris) in the present experiment.…”
Section: Discussioncontrasting
confidence: 99%
“…PUFA n-6/n-3 ratio established in the present experiment (5.6 in the muscle tissue, 4.2 in the VAT) is within the range of the results of the recent similar experiments in pigs fed diets containing fish oil: 6.39 in the outer shoulder fat layer (Hallenstvedt et al 2012), and 3.57 and 3.11 in the muscle (m. triceps brachii) and backfat, respectively (Lisiak et al 2013), or 3.51 and 3.99 in the muscle tissue (m. longissimus dorsi) and subcutaneous fat, respectively (Wojtasik et al 2012). However, in the two last-mentioned experiments reporting lower PUFA n-6/n-3 ratios (Wojtasik et al 2012;Lisiak et al 2013), in addition to fish oil the authors used also linseed oil, which has a very high content of α-linolenic acid; though a conversion efficiency of dietary ALA to the tissue LC-PUFA n-3 is very low (Komprda et al 2013), ALA itself is efficiently transported from a diet to the animal (pig) tissues (Skiba et al 2015) and therefore substantially decreases the total PUFA n-6/n-3 ratio.…”
Section: Discussionsupporting
confidence: 83%
“…Similar findings were presented by Duran-Montgé et al (2010). Some researchers (Nguyen et al, 2003a;Kloareg et al, 2007;Duran-Montgé et al, 2010;Raj et al, 2010;Wojtasik et al, 2012), however, pointed to a possibility of differences between intramuscular (e.g., in MLD) and subcutaneous fat in terms of the intensity with which their EPA, DPA and DHA contents increased, even though the concentrations of linoleic and linolenic acids were significantly higher in the subcutaneous than in intramuscular fat. Tissue differences in the content of linoleic and linolenic acids can be explained by the different levels of incorporation of these fatty acids into them.…”
Section: Discussionsupporting
confidence: 74%
“…Admittedly, the muscle of pigs of the control group had less intramuscular fat than the experimental pigs, but this difference was insignificant. In contrast, Nguyen et al (2003a) and Wojtasik et al (2012) found no differences in the intramuscular fat of the MLD in animals fed similarly as ours.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation